The paradoxical moderating effects of metacognition in the relationships between self-esteem, depressive symptoms, and quality of life in anorexia and bulimia - Cassi R. Springfield; Kelsey A. Bonfils; Nikita V. Chernov; Tatyana V. Moiseeva; Marta V. Sozinova; Nadezhda G. Dmitryeva; Paul H. Lysaker; Olga A. Karpenko; George P. Kostyuk (Consortium Psychiatricum, 2023)
BACKGROUND: Self-esteem and depressive symptoms contribute to a lower quality of life in people suffering from eating disorders. However, limited research has examined whether other factors may affect how these variables influence one another over time. Metacognition is a previously unexplored determinant that may impact the relationships between self-esteem, depressive symptoms, and quality of life in instances of eating disorders.